2019
DOI: 10.1007/s11665-019-04417-0
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Ti-Nb Alloys Prepared by Mechanical Alloying and Spark Plasma Sintering

Abstract: The effect of Nb content on microstructure, mechanical properties and superelasticity was studied in Ti-Nb alloys fabricated by powder metallurgy route using mechanical alloying and spark plasma sintering. In the microstructure of the as-sintered materials, undissolved Nb particles as well as precipitations of a-phase at grain boundaries of b-grains were observed. In order to improve the homogeneity of the materials, additional heat treatment at 1250°C for 24 h was performed. As a result, Nb particles were dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…This value was associated mainly with the R E part, as a result of the low elastic modulus (25 GPa) and high YS (above 1000 MPa). In our previous work [ 12 ], we also showed 3% of recoverable strain for sintered Ti-14Nb alloy, however, this value was related mainly to the R E part because of the high YS (920 MPa) of the alloy.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…This value was associated mainly with the R E part, as a result of the low elastic modulus (25 GPa) and high YS (above 1000 MPa). In our previous work [ 12 ], we also showed 3% of recoverable strain for sintered Ti-14Nb alloy, however, this value was related mainly to the R E part because of the high YS (920 MPa) of the alloy.…”
Section: Resultsmentioning
confidence: 68%
“…The found orientation relationship was . Although the ω phase is metastable under ambient conditions, it is typically observed in Ti-Nb alloys in the form of nanometric precipitations uniformly distributed in the matrix [ 12 , 36 , 37 ]. The presence of these precipitations mechanically suppresses the martensitic transformation, but, on the other hand, it increases the critical stress for slip deformation which is low for single-phase Ti-Nb alloys [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a wear process that take place during the milling, the WC phase was introduced to the particles. As described in our previous work [ 18 ] the amount of the carbides increases with the increasing milling time, therefore the intermediate synthesis time of 30 h was selected in order to avoid the extensive contamination and to obtain a satisfactory level of the mixing of the elemental powders.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the superelastic properties were observed in sintered Ti-13Nb and Ti-11Nb alloys containing 2.5 and 4.0 at.% of oxygen, respectively [ 16 , 17 ]. Similarly, our previous studies on the spark-plasma sintered Ti-Nb alloys, showed that in order to obtain the superelastic properties, the concentration of Nb has to be reduced from the initial 26 to 14 at.% [ 18 ].…”
Section: Introductionmentioning
confidence: 97%